2004
DOI: 10.1002/qua.20359
|View full text |Cite
|
Sign up to set email alerts
|

Accurate heats of formation and acidities for H3PO4, H2SO4, and H2CO3 from ab initio electronic structure calculations

Abstract: Ϫ were calculated using coupled cluster theory including noniterative, quasi-perturbative triple excitations (CCSD(T)) with large basis sets. Optimized geometries and harmonic vibrational frequencies were calculated at the MP2/aug-cc-pVTZ level. Atomization energies were obtained by extrapolating CCSD(T) valence energies to the complete basis set limit (CBS) using the aug-cc-pV(nϩd)Z (n ϭ D, T, Q) basis sets where the ϩd corresponds to the inclusion of tight d functions for the second row atoms P and S. In ord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
49
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 61 publications
4
49
0
Order By: Relevance
“…, in good agreement with their own experimental observation that the gas-phase acidity of phosphoric acid lies between those of HCl and HBr [35]. Our own theoretical estimates (Table 2) compare favorably with this finding and a very high level ab initio value of Alexeev et al [36] of PA ϭ 1376 kJ mol Ϫ1 , compared to our "best" estimate (G3) of PA ϭ 1376 kJ mol Ϫ1 . The proton affinity seems to be quite unaffected by dimethylation; our calculations at the RI-MP2/ Table 2).…”
Section: Methodssupporting
confidence: 91%
“…, in good agreement with their own experimental observation that the gas-phase acidity of phosphoric acid lies between those of HCl and HBr [35]. Our own theoretical estimates (Table 2) compare favorably with this finding and a very high level ab initio value of Alexeev et al [36] of PA ϭ 1376 kJ mol Ϫ1 , compared to our "best" estimate (G3) of PA ϭ 1376 kJ mol Ϫ1 . The proton affinity seems to be quite unaffected by dimethylation; our calculations at the RI-MP2/ Table 2).…”
Section: Methodssupporting
confidence: 91%
“…This is further supported by knowing that Morris et al determined the Δ G acid of H 3 PO 4 between 318.1 to 327.9 kcal mol −1 , while NIST Database reports the value of Δ H acid = 330.5 ±5 kcal mol −1 . Also, the G4‐computed Δ H acid and Δ G acid values for H 3 PO 4 are 329.1 and 322.1, respectively, while Alexeev et al reported values of 328.8 and 322.2 kcal mol −1 using MP2 calculations.…”
Section: Resultsmentioning
confidence: 99%
“…In the gas phase, the phosphate groups being the lipids A most acidic sites [21], a distant double deprotonation can occur regioselectively on these sites to give rise to the formation of the doubly charged [M PP − 2H] 2− lipid A (i.e., m/z 897.6), as displayed in the ESI mass spectrum (Fig. 2 The lack of resolution for the signal at m/z 897.6 as compared to the m/z 792.5 ion can be explained by considering that this doubly charged ion is somewhat unstable and may decompose promptly by application of the axial modulation during the analytical scan [27][28][29][30] into the ion trap analyzer.…”
Section: Optimization At Medium M/z Values Of Mass Spectrum: Discrimimentioning
confidence: 99%
“…Lipid A contains one or two phosphoryl group(s), considered to be very acidic in the gas phase [21]. The phosphate substitute(s) the N-acetylglucosamine disaccharide at the C-1 and/or C-4 position(s).…”
mentioning
confidence: 99%